The Impact of Electronic Word of Mouth (E-WOM), Brand Image, and Brand Awareness on Consumers’ Purchase Intention of Adidas Samba Shoes - Putri Berliani Pangestu; Wala Erpurini (Jurnal Administrasi Bisnis, 2025)
This study aims to analyze the influence of electronic word of mouth (e-WOM), brand image, and brand awareness on purchase intention for Adidas Samba shoes in Cimahi City. The background of this study is based on the phenomenon of the decline in Adidas’s Top Brand Index in recent years, which indicates a decrease in consumer interest and loyalty. The research method used is a quantitative method with a descriptive and verifiable approach. Data were collected through the distribution of questionnaires to respondents who are consumers or potential consumers of Adidas Samba shoes in Cimahi City. The data analysis techniques used include validity and reliability tests, classical assumption tests, and multiple linear regression analysis to test the hypotheses. The results of the study indicate that electronic word of mouth, both partially and simultaneously, has no positive and significant effect on purchase intention; however, brand image and brand awareness, both partially and simultaneously, have a positive and significant effect on purchase intention. The variable with the most dominant influence is brand image, indicating that brand image plays a crucial role in enhancing consumer purchase interest.